2015
DOI: 10.5371/hp.2015.27.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Insufficiency Fracture around Radiographically Loose Cemented Stem: A Report of Two Cases

Abstract: As the osteoporotic patient population grows, various periprosthetic fractures that cannot be classified appropriately can occur around the femur after hip arthroplasty. We experienced two cases of periprosthetic insufficiency fractures at subtrochanteric area of the femurs around radiographically loose cemented femoral stems. The ages of the patients were 75 years and 83 years. Both patients could not recall any history of trauma before the onset of pain. Both were treated non-operatively. Both healed unevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In principle, the plate should be of sufficient length for firm fixation because a longer plate with empty screw holes at the fracture site provides a longer working length than a short plate. Previous reports recommend that the plate used for internal fixation must be of sufficient length to allow as much overlap of the femoral stem as possible1222). A longer plate ending near the end of the bone is preferable to the one ending in the metadiaphyseal zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the plate should be of sufficient length for firm fixation because a longer plate with empty screw holes at the fracture site provides a longer working length than a short plate. Previous reports recommend that the plate used for internal fixation must be of sufficient length to allow as much overlap of the femoral stem as possible1222). A longer plate ending near the end of the bone is preferable to the one ending in the metadiaphyseal zone.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of prognostic factors relating to the treatment of PFF using cable-plates was lacking. The treatment of PFFs requires particular care because stable fixation is difficult in this situation as compared to ordinary fractures; significant effort has been spent to properly classify and treat PFFs1112). The purpose of this study was to assess clinical outcomes and analyze potential prognostic factors in the treatment of PFFs using the cable-plate construct.…”
Section: Introductionmentioning
confidence: 99%
“…We found only 3 reports of stress fractures occurring around femoral stems [ 6 – 8 ]. Chun et al reported 2 cases of insufficiency fractures located at the subtrochanteric area of loose, cemented stems [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found only 3 reports of stress fractures occurring around femoral stems [ 6 – 8 ]. Chun et al reported 2 cases of insufficiency fractures located at the subtrochanteric area of loose, cemented stems [ 6 ]. The authors alleged that osteoporotic bones of elderly patients might produce atraumatic, atypical femoral fractures different to that of the ones reported with bisphosphonate therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation